PREVALÊNCIA DA BRUCELOSE CANINA NA MICRORREGIÃO DA SERRA DE BOTUCATU, SÃO PAULO, BRASIL - Moraes, C.c.g. [UNESP] (2024)
The prevalence of anti-Brucella canis serum antibodies was studied in dogs of the microregion of the Botucatu mountain range, São Paulo State, Brazil, through the rapid slide agglutination test (SAT),and the modified 2mercaptoethanol rapid slide agglutination test (ME-SAT). No expressive divergence between animals sex and origin areas was observed. Positive results was verified in 19 dogs in the SAT (1.77%) and nine in the ME-SAT (0.84%)..